Accounting for Management Practices: A Holistic Perspective in Nepalese Commercial Banks - Gnawali, Achyut (Saptagandaki Journal, 2021)
Background: Management Accounting supports competitive decision-making by collecting, processing, and communicating information. It helps in management plan, control, and evaluation of business practices in Nepalese Commercial Banks. The main aim of this study is to analyze the management accounting system practices in Nepalese Commercial Banks. Methods: This study followed a descriptive research design. A sample of 507 bank employees has been selected with convenience sampling technique to get the information related to the accounting practices. A structured questionnaire related to the Management Accounting System including the five domains like Budgeting and Planning, Controlling and Reporting, Decision support system, Costing system and Performance Evaluation were designed in Likert scale rating format for responses, and descriptive statistics were used to make the analysis of responses. Results: It was found that the Nepalese banking sectors apply management accounting practices including budgeting and planning, controlling and reporting, decisions making, costing and performance evaluations. Among the various techniques banking sector use Budgeting and control most and costing system the least. These techniques were widely used in bank's performance evaluation as well. Conclusion: there is a positive and significant association between the application of management accounting system and organizational performance. So, the banks can enhance their performance through the use various techniques of accounting for managerial decisions.